Modeling the impact of technological change on nutrition and marketed surplus - Ahmed, M.M.; Preckel, P.; Baker, T.G.; López Pereira, M.A. (Elsevier, 2001)
This study develops and demonstrates procedures for modeling the impact of agricultural technology adoption decisions on consumption and nutrition in a subsistence-farming context. The method is based on expected direct utility maximization (EDUM) formulation and incorporates subsistence quantities for broad aggregates of protein, calories, and other consumption goods. The method is applied to a hillside farming system of southern Honduras where new sorghum cultivars and erosion control techniques are being introduced. The expected direct utility maximization model allows the estimation of the effects of new technology on consumption and marketed surplus in situations where marginal values of products vary by state of nature and are affected by consumption and production choices. The introduction of the new technologies in southern Honduras results in improved nutrition and substantial increases in marketed surplus. These effects are due to simultaneous changes in output and consumption patterns. This work extends the subject of household modeling to problems with risk, and thus complements prior work in both the integrated analysis of production/consumption decisions and stochastic decision analysis.